2019
DOI: 10.3389/fpsyt.2018.00780
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation of Breathing as an Adjunctive Treatment of Insomnia

Abstract: Sleep is a quiescent behavioral state during which complex homeostatic functions essential to health and well-being occur. Insomnia is a very common psychiatric disorder leading to a myriad of detrimental effects including loss of concentration, memory, and performance as well as disease. Current pharmaceutical treatments can be expensive, impairing, unhealthy, and habit-forming. Relaxation techniques, such as meditation target the brain and body in contrast to pharmaceutical interventions which solely target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 103 publications
0
25
0
1
Order By: Relevance
“…Yang, Y., S., et al, [28] examined the effect of exercise on sleep quality in pregnant woman, they reported that relaxation exercise as youga or breathing exercise and aerobic exercise is one of the non-pharmacological nursing intervention that will reduce insomnia and anxiety. On the other hand, Jerath, R., et al [29] reported that breathing exercise result in stronger sympatho-inhibition that lead to reduction in pain intensity, dyspnea among asthmatic patient, improves cardiorespiratory synchronization and improves mood disorders which intern improves sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Yang, Y., S., et al, [28] examined the effect of exercise on sleep quality in pregnant woman, they reported that relaxation exercise as youga or breathing exercise and aerobic exercise is one of the non-pharmacological nursing intervention that will reduce insomnia and anxiety. On the other hand, Jerath, R., et al [29] reported that breathing exercise result in stronger sympatho-inhibition that lead to reduction in pain intensity, dyspnea among asthmatic patient, improves cardiorespiratory synchronization and improves mood disorders which intern improves sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…These body rhythms are always present with us, slowly provoking certain mental states, and so they deserve attention from not only those in health care but also the average person who would benefit from the ability to regulate emotional state. We and others have suggested that long-term "negative" body rhythms can keep us trapped in a vicious cycle of poor emotional health, which also leads to physical health declines (Jerath et al, 2019).…”
Section: Emotion the Nervous System And The Mind-body Responsementioning
confidence: 99%
“…Jereth et al present an interesting perspective on the influences of autonomic nervous system (ANS) on sleep onset latency, duration, and quality [20]. Their dysevolution theory proposes that the chronic sympathetic hyperactivation and/or parasympathetic hypoactivation disrupts sleep [20][21][22]. Monitoring heart rate variability (HRV) and respiratory sinus arrhythmia (RSA) is the current standard for studying the role and impact of ANS on sleep architecture.…”
Section: Discussionmentioning
confidence: 99%